PICK'S FORMULA AND GENERALIZED EHRHART QUASI-POLYNOMIALS - Takayuki Hibi; Miyuki Nakamura; Ivana Natalia Kristantyo Samudro; Akiyoshi Tsuchiya (IndoMS, 2015)
By virtue of Pick's formula, the generalized Ehrhart quasi-polynomial of the triangulation P R^2 with the vertices (0,0), (u(n),0), (0,v(n)), where u(x) and v(x) belong to Z[x] and where n=1,2, …, will be computed.DOI : http://dx.doi.org/10.22342/jims.21.2.192.71-75